Optimize flotation process of Mo–Bi sulfide ore for cleaner production. (1st April 2021) - Lin, Shangyong; Liu, Runqing; Hu, Yuehua; Sun, Wei; Shi, Zhizhong; Han, Haisheng; Li, Wenheng
Abstract: An economical and environmentally friendly beneficiation process is of great practical significance for the mining industry to achieve green and sustainable development. This study aims to optimize the traditional flotation process of Mo–Bi sulfide ore by using the difference in natural floatability of minerals for cleaner production. Single-mineral flotation tests demonstrate that the natural floatability of the sulfide minerals investigated decreased in the following order: molybdenite > bismuthinite > pyrite. Molybdenite displayed the best natural floatability in a wide pH range, and pyrite exhibited the least naturally floatable under alkaline conditions. The moderately natural floatability of bismuthinite was observed at the pH below 6, but decreased with the shift of pH to the alkaline region. Batch flotation tests indicate that the collectorless flotation of Mo–Bi sulfide ore resulted in lower flotation kinetics but higher selectivity than those of the collector flotation process. Industrial-scale tests illustrate that introducing collectorless flotation into the sequential flotation in industrial production was a feasible and reliable method of simultaneously increasing economic benefits and improving product quality. The grades of the Mo and Bi concentrates generated from the modified flotation process were 2.78% and 2.81% higher than those produced by the traditional flotation process. The daily consumption of chemical reagents in the modified flotation process decreased by more than 10%, reducing the annual cost of flotation reagent by approximately USD 60407.0. Given the characteristics of low reagents dosage, slightly environmental pollution, and high economic benefits, the modified flotation flowsheet is a promising separation process that can be extensively employed for mineral sources with similar mineralogical properties. Graphical abstract: Image 1 Highlights: Natural floatability order, molybdenite > bismuthinite > pyrite. Collectorless flotation resulted in lower flotation kinetic but higher selectivity. Industrial application of collectorless flotation improve quality of final products. Industrial application of collectorless flotation decreases environmental pollution.